Metal-support interaction of NI-supported palm oil fuel ash catalyst produced from self-combustion technique for methane cracking - Asmida, Ideris
Methane cracking is an excellent route for CO-free H2 production. During methane cracking, Ni-supported catalysts synthesized using conventional impregnation method are usually suffered from non-uniform distribution and agglomeration thus affected its stability. A self-combustion catalyst preparation technique; in situ glycine-nitrate combustion process (in situ GNP) has been explored with the aim of producing metal-supported catalysts with strong metal-support interaction, thus highly dispersed catalyst. In the meantime, an approach of utilizing biomass wastes for catalytic purposes seems to be promising. In this work, palm oil fuel ash (POFA) has been explored as a catalyst support in methane cracking due to its high SiO2 content. Ni catalyst supported on palm oil fuel ash (Ni–POFA) has been prepared using in situ GNP and its catalytic activity of the catalysts was evaluated for methane cracking at 550°C. Effects of pre-treatment, catalyst preparation method, Ni loading and gas-space hour velocity (GHSV) have been investigated and POFA and Ni–POFA catalysts characterizations were performed using XRF, XRD, BET, FESEM, TGA and H2-TPR. Pre-treatment has improved SiO2 composition in POFA from 42.4 to 72.0%. A decent CH4 conversion achieved by Ni–POFA catalyst produced using POFA treated with citric acid can be ascribed to high SiO2 content, reasonable surface area, and moderate POFA porous structure. For catalyst preparation, Ni–POFA produced from in situ GNP has better H2 yield than one produced using impregnation. High Ni dispersion has provided more availability of Ni active sites on POFA support, thus resulted in higher H2 yield. Additionally, the catalyst preparation method influenced the morphology of the catalyst and the type of carbon formed on the spent Ni–POFA catalysts. At the optimum GHSV of 22,500 mL/g.h,15 wt.% Ni–POFA catalyst offered the highest catalyst stability with highest initial CH4 conversion and H2 yield of 87.0% of and 27.0%, respectively. As a conclusion, this project has successfully produced a stable Ni catalyst supported on palm oil fuel ash (Ni–POFA) with a decent catalytic activity for methane cracking process.